A Prospective Observational Study Combinition of Proton Pump Inhibitors with Prokinetics in Gerd - Zobia Mushtaq, Bushra Adeel, Tanveer Hussain, Mazhar Ali, Muhammad Ayyaz, Imran Joher (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Gastroesophageal reflux disease (GERD), a fairly common ailment that has a negative influence on quality of life. 30- 40% of patients with GERD have an insufficient response to standard PPIs therapy. For subjects resistant to this PPI therapy, double the PPI dosage or switch to different PPIs, which may not be ideal. So, combination therapy with prokinetic agent will significantly improve GERD symptoms. Study Design: A prospective observational study. Place and Duration: In the Department of Medicine, Faisalabad Medical University, Faisalabad from May 2022 to July 2022. Material and methods: 130 patients with suggestive symptoms of GERD were included to evaluate overlap between GERD and delayed gastric emptying and to forecast the necessity for therapy in combination with prokinetic drugs using the Frequency Scale for the Symptoms of GERD (FSSG) score. Results: 17.20 ± 8.40 was the mean total score of FSSG. Of the 130 subjects, 106 (81.54%) patients have GERD symptoms with an overall FSSG score >8. 7.43 ± 4.08 was the mean reflux score, and 9.40 ± 5.30 was the mean dysmotility score. In this analysis, patients with GERD symptoms had high score of FSSG, the symptoms of dysmotility appeared to be the main symptom than acid reflux. Conclusions: Based on this analysis results, combination therapy with prokinetic and PPIs in the subgroups of subjects with high scores of FSSG improved GERD symptoms. Keywords: Dysmotility score, delayed gastric emptying, GERD and Reflux score.